CFD analysis of the supersonic nozzle flow with sudden expansion - Ahmed, Khizar Pathan; Dabeer, P.S.; Khan, Sher Afghan (International Organization of Scientific Research ( IOSR ), 2016)
This paper presents the Computational Fluid Dynamic (CFD) analysis to study the effect of area ratio and nozzle pressure ratio on the flow field of axi-symmetric sudden expansion from convergent-divergent nozzles to a circular duct of larger cross-sectional area than that of nozzle exit area. The study is focusing on the pressure and velocity distribution along axial length. The analysis is done by varying the area ratios and nozzle pressure ratios. The area ratios for the analysis are 1, 2, 4, 6, 8 and 10. The values of nozzle pressure ratios considered are 2, 4, 6, 8 and 10. The results are plotted with the help to graphs. By observing all the results it can be concluded that the flow field in enlarged duct is much affected by area ratio.